Recent Developments in the Detection of Zn2+ Ions Using Schiff Base Probes - Kumar, Ram; Singh, Bholey; Pandey, Shwetank Shashi; Pani, Balaram (SynOpen, 2023)
In the past few decades, zinc has attracted great attention from the scientific community due to its supreme importance in living organisms. Zinc is a trace element that is vitally important to all living organisms and it plays an important role in the immune system, wound healing, growth, and division. Therefore, the development and advancement of simple, efficient, selective, and inexpensive chemosensors for the determination of Zn2+ is a paramount prerequisite. Chemosensors have unique properties that are used for the specific and selective determination of several metal ions. This review summarizes the Schiff base chemosensors designed and synthesized by several research groups from the year 2018. The interaction of these probes with zinc metal ions has also been discussed briefly in this review. Furthermore, the comparison of detection limits of these probes demonstrated that the Schiff base probe possessing two benzothiazole moieties exhibits the lowest detection limit (0.00028 μM), indicating it to be the lead compound in the determination of Zn2+ ions in the near future.
Keywords: chemosensors; detection; probes; zinc; Schiff base